Efficacy and safety of virgin coconut oil and king coconut oil compared to liquid paraffin as a moisturizer for mild atopic dermatitis: A pilot study: Fonseka S.1*, Gnanarathne S.1, Manathunga S.1 Yalegama L.L.W.C.2 and Idirisinghe I.M.S.K.2 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Atopic dermatitis is a chronic skin condition due to altered skin barrier. There is no cure for the condition, but it can often be managed with proper care and treatment. Application of a moisturizer is a mainstay of treatment to manage the condition. Therefore, this study assessed the effectiveness and safety of virgin coconut oil (VCO) and king coconut oil (KCO) compared to liquid paraffin as a moisturizer for mild atopic dermatitis. The study was conducted as a pilot study of a randomized, double-blind, parallel group comparison trial on patients with mild atopic dermatitis. Patients were randomized to receive VCO, KCO or liquid paraffin. The outcome measures were SCORing atopic dermatitis (SCORAD) index and Patient Oriented Eczema Measure (POEM) score and instrumental measurements of skin moisture and skin lipid levels at two weeks intervals for 3 times. The results showed a significant improvement of eczema was seen in relation to SCORAD index and POEM scores in all three arms. Significant improvement of moisture levels was seen in KCO and liquid paraffin arms. However, no improvement of lipid levels was seen in all three arms. It was concluded that, this pilot study shows that VCO, KCO and liquid paraffin are equally effective moisturizers for the treatment of mild atopic dermatitis. VCO and KCO can be used instead of hydrocarbon-based liquid paraffin in the treatment of mild atopic dermatitis as those vegetable oils are relatively inexpensive and widely available in Sri Lanka.